Observation of Top Quark Production in Proton-Nucleus Collisions - (:unkn) unknown (AMER PHYSICAL SOC, 2017)
The first observation of top quark production in proton-nucleus collisions is reported using proton-lead data collected by the CMS experiment at the CERN LHC at a nucleon-nucleon center-of-mass energy of root(S)(NN) = 8.16 TeV. The measurement is performed using events with exactly one isolated electron or muon candidate and at least four jets. The data sample corresponds to an integrated luminosity of 174 nb(-1). The significance of the tt signal against the background-only hypothesis is above 5 standard deviations. The measured cross section is sigma(tt) = 45 +/- 8 nb, consistent with predictions from perturbative quantum chromodynamics.
Keywords: BOSON PRODUCTION; PPB COLLISIONS